Language Management in Arabic Learning for Military Purposes: A Pathway to SDG 4 - Nurmala, Mia; Hamid, M. Abdul; Mustofa, Bisri; Baklizi, Mai Khalied Mahmoud (UIN Sunan Gunung Djati Bandung, 2024)
The pressing challenges of our time necessitate the involvement of Arabic language education in achieving SDG 4: Quality Education, particularly in specialized contexts like the military. This study examines the language management system in military Arabic language education at Pusdik Pengmilum Cimahi, Indonesia. It emphasizes its alignment with SDG 4 through knowledge and skills development, attitude and behavior formation, and physical fitness enhancement. Using an exploratory case study approach, data were collected via observation, interviews, and document analysis and analyzed thematically. The findings reveal that military Arabic education is integrated into the Indonesian Army’s core responsibilities, guided by 12 regulatory mechanisms. These mechanisms ensure a structured approach to curriculum design, learner discipline, and operational readiness. For example, knowledge development enhances Arabic proficiency for specific military purposes, while attitude formation fosters cultural competence essential for global citizenship. This study demonstrates how military Arabic education contributes to quality education outcomes, including linguistic skills and intercultural awareness, aligning with sustainable development goals. It offers practical insights for integrating SDG principles into specialized education systems. This study highlights the role of military Arabic education in achieving SDG 4, offering insights into integrating SDG principles into specialized education. Future research could explore implementation in diverse contexts, evaluate long-term impacts, incorporate educational technology, analyze intercultural effects, and link Arabic education to other SDGs like peace and justice